Entoação regional no português do Brasil - Cunha, Cláudia de Souza (2000)
Describe prosodic marks responsible for the identification of five Brazilian speeches: the Pernambuco speech, the Bahia speech, Rio’s, São Paulo's and Porto Alegre's speeches, spanning three major geographical areas - Northeast to South They are all represented by recordings of male and female subjects of higher educational groups, practicing urban speech and coming from State capitals. Description is supported by experimental analysis and phonological models of the metric auto-segmental theoretical lme. On the acoustical-experimental issue, I characterize the behavior of parameters such as duration, intensity and pitch, usmg CECIL computer program as speech analysis tool and usmg three different methodological procedures: 1) Data analysis from the five cities, collected from direct listening (criteria was the accent perception mark), and collected in ten recordings - five from the NURC Project and five out of a same text, read by an informant of the female sex of each city, 2) Data analysis from the five cities collected according to the context of the occurrence - end of Tonal Unity, with emphasis m the Bahia and Rio speeches, through a corpus of 24 recordings (12 from the NURC Project - three male and three female Rio subjects, also three male and three female Bahia subjects - and 12 out of readings, with equal sex distribution); 3) Comparative analysis of the chosen utterances, with no preoccupation regarding quantity, with the sole purpose of observing the quality of identifying marks of an accent Description shows that when facing the multiplicity of tonal variables some prosodic patterns fundamental to the proper functioning of a language are common to all the samples. The duration parameter is fixed as the identifier of the stressed syllable, the presence of the declination line characterizing the final assertive context, the melodic ascending pre-stressed pattem to the stressed pattern characterizing yes-no questions. On the other hand, results point out that pitch parameters and intensity are the main responsible for regional distinction, determining pre-stressed syllables prominence on Northeastern speeches, of the stressed syllable in Southern speech (Rio Grande do Sul) and conferring some Northeastern and Southern characteristics to São Paulo and Rio’s speeches, which definitely gives them intersection sites attributes. Above all I demonstrate that the phenomena is intermittent, and that although regional speech perception is prosodically comprehensible to most Brazilian Portuguese speakers, there are more coincidences than differences in the tonal field.